Fondo Agropecuario de Emergencias: ¿una herramienta de fortalecimiento al desarrollo rural de los productores rurales? - Vázquez, Lucia (Universidad Nacional del Litoral, 2021)
The objective of the article was to understand the operational structure of the Emergency Agricultural Fund (FAE) that is carried out in Uruguay in the face of an agricultural emergency, particularly emergencies declared in the years of 2018 and 2020, having as a script the understanding of its contribution to the rural development and family production. The methodological strategy is made up of field work, complemented by bibliographic studies. The FAE has proposed improvements to the beneficiaries, among them the contribution to mitigating adverse situations in extreme situations can be observed, but with regard to economic support the interest rate was inadequate and there were logistical problems for the distribution of inputs. It was found that FAE's operational structure has generated support for beneficiaries, particularly family producers, in the face of declared agricultural emergencies, which is interpreted in specific actions for rural development.